2014
DOI: 10.3390/s140203308
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antimicrobial Resistance Patterns and Detection of Virulence Genes in Campylobacter Isolates in Italy

Abstract: Campylobacter has developed resistance to several antimicrobial agents over the years, including macrolides, quinolones and fluoroquinolones, becoming a significant public health hazard. A total of 145 strains derived from raw milk, chicken faeces, chicken carcasses, cattle faeces and human faeces collected from various Italian regions, were screened for antimicrobial susceptibility, molecular characterization (SmaI pulsed-field gel electrophoresis) and detection of virulence genes (sequencing and DNA microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 43 publications
5
41
2
5
Order By: Relevance
“…The increase in resistance rates to tetracyclines of Campylobacter spp. is worrisome and has been constantly described, mainly in animal isolates (GALLAY et al, 2007;SAHIN et al, 2008;CHEN et al, 2010;LEHTOPOLKU et al, 2010;ADZITEY et al, 2012;CHOKBOONMONGKOL et al, 2013;DI GIANNATALE et al, 2014). Resistance to tetracycline has a clinical importance, since tetracycline is considered a second-line treatment for human Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in resistance rates to tetracyclines of Campylobacter spp. is worrisome and has been constantly described, mainly in animal isolates (GALLAY et al, 2007;SAHIN et al, 2008;CHEN et al, 2010;LEHTOPOLKU et al, 2010;ADZITEY et al, 2012;CHOKBOONMONGKOL et al, 2013;DI GIANNATALE et al, 2014). Resistance to tetracycline has a clinical importance, since tetracycline is considered a second-line treatment for human Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…isolates, from both humans and animals, to different classes of antimicrobial agents such as quinolones, macrolides, aminoglycosides, tetracyclines, β-lactams, and sulfonamides has been widely reported ( VAN DEN BOGAARD;STOBBERINGH, 2000;CHUMA et al, 2001;AVRAIN et al, 2003;TREMBLAY et al, 2003;MIRANDA;LAGE, 2007;ABAY et al, 2014;DI GIANNATALE et al, 2014). Nonetheless, mainly the resistance to quinolones and macrolides has been considered an emerging public health hazard, due to its fast increase in the last decades (GIBREEL; TAYLOR, 2006;FITZGERALD et al, 2008;GARCIA-MIGURA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…29 More specifically considering the virulence mechanisms for the pathogenesis of Campylobacter spp. during human infections, these might contribute to their flagella-mediated motility, adherence to the intestinal mucosa, invasive capability, and production of toxins.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the presence of C. jejuni in in-line milk filters and raw milk confirmed that raw milk consumption is a significant risk factor for human infection in Italy. Further studies have indicated a significant level of resistance to ciprofloxacin (62.8 %), tetracyclines (55.9 %) and nalidixic acid (55.2 %) in isolates of C. jejuni from a variety of animal-related sources, including raw milk, and also from human faeces, although the precise sources of such strains are not provided (Di Giannatale et al, 2014). Outside the EU, in a study in Quebec, Canada, of C. jejuni isolates obtained between 2000 and 2003 from a variety of sources, which included 33 isolates from raw milk, ciprofloxacin resistance was reported to be almost absent in isolates from water, chicken, and raw milk (Levesque et al, 2007).…”
Section: Dairy Cattlementioning
confidence: 99%